2013
DOI: 10.1186/1471-2164-14-402
|View full text |Cite
|
Sign up to set email alerts
|

A unique nucleosome arrangement, maintained actively by chromatin remodelers facilitates transcription of yeast tRNA genes

Abstract: BackgroundRNA polymerase (pol) III transcribes a unique class of genes with intra-genic promoters and high transcriptional activity. The major contributors to the pol III transcriptome, tRNAs genes are found scattered on all chromosomes of yeast. A prototype tDNA of <150 bp length, is generally considered nucleosome-free while some pol III-transcribed genes have been shown to have nucleosome-positioning properties.ResultsUsing high resolution ChIP-chip and ChIP-seq methods, we found several unique features ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 52 publications
9
94
0
Order By: Relevance
“…Meta-analysis of this dataset showed that SUMO overlaps the transcription unit of tRNA genes, forming a peak right at the transcription start site (TSS; Fig. 2B), resembling previously published meta-analyses of the chromatin localization of RNAPIII and its nascentome (14,15). These high-throughput data were validated by ChIP followed by quantitative PCR (ChIP-qPCR) using primers specific for a panel of RNAPIIItranscribed genes (Fig.…”
Section: Significancesupporting
confidence: 81%
“…Meta-analysis of this dataset showed that SUMO overlaps the transcription unit of tRNA genes, forming a peak right at the transcription start site (TSS; Fig. 2B), resembling previously published meta-analyses of the chromatin localization of RNAPIII and its nascentome (14,15). These high-throughput data were validated by ChIP followed by quantitative PCR (ChIP-qPCR) using primers specific for a panel of RNAPIIItranscribed genes (Fig.…”
Section: Significancesupporting
confidence: 81%
“…It is known that RNAP III-transcribed genes are free of nucleosomes during repression. 46 The much longer RNAP II-transcribed genes have developed intricate ways to regulate the activity of nucleosomes that occupy their lengths. The TFIIIB/C-tRNA gene complexes occupy a DNA length similar to nucleosomes, although perhaps more stably so.…”
Section: Tfiiic Dynamics: a Trna Gene Guardian?mentioning
confidence: 99%
“…One of the most unexpected findings of ChIP-seq profiling in human cells was the large number of annotated loci devoid of Pol III [20,22,24,30], a situation that strictly differs from the uniform binding pattern observed in yeast [14][15][16][17]. In immortalised human fibroblasts (IMR90hTert) grown under multiple conditions, Pol III was absent from $32% of annotated loci [30], suggesting that a large fraction of Pol III genes is in a permanently repressed state.…”
Section: A Large Fraction Of Pol III Loci Is Silentmentioning
confidence: 99%
“…Genome-wide analyses to identify in vivo Pol III binding sites were first carried out in S. cerevisiae by the mean of chromatin immunoprecipitation (ChIP). With this approach, DNA is cross-linked to Pol III or its general transcription factors (GTFs), immunoprecipitated, and subjected to microarray {ChIP-chip [14][15][16]} or next generation sequencing {ChIP-seq [17]} analysis. These experiments revealed Pol III binding at the vast majority of known targets and an overall correlation with transcription as determined by measurement of the corresponding RNA levels.…”
Section: Chip-seq Reveals Pol III Binding Dynamics In Multiple Eukarymentioning
confidence: 99%